CRYPTOCURRENCY: ERA AND FIELD OF FINANCIAL INNOVATIONS - V. Korneev; О. Cheberyako (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
Essence of cryptocurrencies is considered in the article, their risks and prospects of development in Ukraine and world. Advantages and disadvantages of crypto currency are described. Positions of foreign central banks and other financial regulators are lighted up in relation to cryptocurrencies and markets of cryptocurrencies. It is offered, that the experience of Japan, Switzerland, the United States and England in this question should be used as a fairway. It is marked that corresponding activity and financial services must be licensed by the state as a type of professional activity on the stages of formation of cryptocurrency (mining) and support of its circulation (trading and financial consulting).